Clothing needs of teenage girls (Journal of the College of Basic Education, 2025)
The aim of the research was to study the desire to select ready-made clothes available in local markets and then identify the trend towards ready-made clothing designs available in local markets and finally identify the colors of clothing preferred by teenage girls at this stage, the sample of the study was represented by teenage students (12-21) years old in secondary schools on both sides of Karkh and Rusafa from Baghdad governorate, a questionnaire consisting of (24) paragraphs was the results came that teenagers prefer clothes that keep up with the latest international fashions with high prices, which are characterized by elastic and Matching the body size and the personality of the girl with colors that match the skin color even if it is multiple to more than one color, as well as characterized by simplicity and lack of complexity, bags and shoes are chosen based on the shape and not the price, and they prefer accessories and clothing supplements in a limited way